Elevated serum nuclear factor erythroid 2-related factor 2 levels contribute to a poor prognosis after acute supratentorial intracerebral hemorrhage: A prospective cohort study - Wang, Chuan-Liu; Yan, Xin-Jiang; Zhang, Cheng-Liang; Xu, Yan-Wen (Frontiers in Aging Neuroscience, 2022)
Objective: Nuclear factor erythroid 2–related factor 2 (Nrf2) is a key transcriptional factor for antioxidant response element-regulated genes. The purpose of this study was to assess the prognostic role of serum Nrf2 in intracerebral hemorrhage (ICH). Methods: In this prospective, observational study, serum Nrf2 levels of 115 acute supratentorial ICH patients and 115 controls were gauged. Early neurologic deterioration (END) was defined as an increase of 4 or greater points in National Institutes of Health Stroke Scale (NIHSS) score or death at post-stroke 24 hours. A poor outcome was referred to as post-stroke 90-day modified Rankin scale score of 3-6. END and a poor outcome were considered as the two prognostic parameters. Results: As compared to controls, serum Nrf2 levels of patients were substantially elevated (P<0.001), with its levels increasing during the 6-h period immediately, peaking in 12-18 h, plateauing at 18-24 h, decreasing gradually thereafter (P<0.05). Serum Nrf2 levels of patients were independently correlated with NIHSS score (t=3.033; P=0.003) and hematoma volume (t=3.210; P=0.002), independently predicted END (odds ratio, 1.125; 95% confidence interval, 1.027-1.232; P=0.011) and poor outcome (odds ratio, 1.217; 95% confidence interval, 1.067-1.387; P=0.013), as well as efficiently distinguished END (area under curve, 0.771; 95% confidence interval, 0.666-0.877; P<0.001) and poor outcome (area under curve, 0.803; 95% confidence interval, 0.725-0.882; P<0.001). Its predictive ability was equivalent to those of NIHSS score and hematoma volume (both P>0.05), and it also significantly improved their predictive abilities under receiver operating characteristic curve (all P<0.05). Conclusion: Elevated serum Nrf2 levels are closely correlated with severity, END and 90-day poor outcome following ICH. Hence, Nrf2 may play an important role in acute brain injury after ICH and serum Nrf2 may have the potential to serve as a prognostic biomarker of ICH.